Impact of Evaluation of Tumour Grade by Core Needle Biopsy on Clinical Risk Assessment and Patient Selection for Adjuvant Systemic Treatment in Breast Cancer - Saqib Ali, Syeda Javeriya Saeed, Sadaf Zahid, Isbah Rashid, Fahmida Khatoon, Tahani Nasser Altamimi, Ruba Mustafa Alsaid Ahmed, Rashid Dhaher Alshammari, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Breast cancer is one of the most common cancers affecting women worldwide. The prognosis and treatment of breast cancer depend largely on various prognostic factors, including tumour grade, hormone receptor status, and HER2/neu overexpression. Objectives: The main objective of the study is to find the impact of evaluation of tumour grade by core needle biopsy on clinical risk assessment and patient selection for adjuvant systemic treatment in breast cancer Material and Methods: This retrospective cohort study was conducted in Services Hospital, Lahore during January 2020 to January 2021. The study participants were women with breast cancer who underwent core needle biopsy for tumour grade evaluation at a single institution during the study period. Results: Of the 70 patients included in the study, the mean age was 58 years (range, 32-85 years), and the majority were postmenopausal (60%). Most patients had invasive ductal carcinoma (IDC) (85%), and the remainder had invasive lobular carcinoma (ILC) (15%). Most patients had stage II (45%) or stage III (35%) breast cancer at the time of diagnosis. All patients underwent core needle biopsy for tumour grade evaluation. Conclusion: In conclusion, the study supports the use of core needle biopsy as a reliable method for evaluating tumour grade in breast cancer patients. Further research is needed to evaluate the long-term outcomes of patients who are treated based on tumour grade assessed by core needle biopsy.